How and when team regulatory focus influences team innovation and member creativity. Issue 1 (5th February 2018) - Li, Ci-Rong; Li, Chun-Xuan; Lin, Chen-Ju
Abstract : Purpose: The purpose of this paper is to test how team regulatory focus may relate to individual creativity and team innovation; and address the fit/misfit issue of team regulatory focus and team bureaucracy. Design/methodology/approach: The authors collected data from 377 members and their leaders within 56 R&D teams in two Taiwanese companies. Findings: A team promotion focus was positively related, whereas a team prevention focus was negatively related, to both team innovation and member creativity through team perspective taking and employee information elaboration, respectively. Furthermore, team bureaucracy played a moderating role that suppressed the indirect relationship between team regulatory focus and creativity. Originality/value: This is one of first studies to explore an underlying mechanism linking team regulatory focus and both team innovation and member creativity. The authors provide a more complete view of the creative and innovation implications of team-level self-regulation.